2015
DOI: 10.1093/bja/aev042
|View full text |Cite
|
Sign up to set email alerts
|

Performance of influenza-specific triage tools in an H1N1-positive cohort: P/F ratio better predicts the need for mechanical ventilation and critical care admission

Abstract: The P/F ratio was a better predictor of need for mechanical ventilation than STSS. The P/F ratio is a simple and accepted determinant of hypoxaemia and should be used if secondary triaging becomes necessary during future influenza pandemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…[3][4][5][6][7] There is little doubt that the profession has benefited from such monitoring of performance, but the true beneficiaries of clinical governance have been our patients. 6 An article published Editorials | 867…”
Section: Declaration Of Interestmentioning
confidence: 99%
See 4 more Smart Citations
“…[3][4][5][6][7] There is little doubt that the profession has benefited from such monitoring of performance, but the true beneficiaries of clinical governance have been our patients. 6 An article published Editorials | 867…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Indeed, even at a unit population level they are outperformed by the subjective judgement of clinicians. 12 The receiver operating characteristic curves in the study reported in this edition 7 illustrate the problem with these triage tools. Whilst the diagnostic performance is good, with an area under curve of >0.8 for the best-performing measures, even at the optimal cut-off the measures are some considerable distance from 100% sensitivity and specificity for admission to intensive care, let alone prediction of mortality.…”
mentioning
confidence: 95%
See 3 more Smart Citations